EXPECTATION GAP ANTARA AUDITOR DAN MAHASISWA AKUNTANSI - Sukadwilinda, Sukadwilinda; Susanto, Bambang (Universitas Pendidikan Indonesia, 2014)
Abstract. This study aimed to get empirical evidence about perceptions between auditors and accounting students to Expectation gap in the issue of the auditor and the audit process, the auditor's responsibilities , attributes the performance of auditors and audit results communications. The method used in this research is a comparative descriptive . The respondent in this study was 30 Auditor on public accounting firm in Bandung and 30 students of Accounting at the University of Buana YPKP bandung and Maranatha University Bandung . For processing such data used Mann Whitney test ( U test ). Based on the results of the study indicate that there are significant differences in perceptions between auditors and accounting students on the issue of the auditor and the audit process , as well as the communication of audit results. As for the issue of the responsibility of the auditor and the auditor 's performance attributes there is no significant difference between the auditor and accounting students.Keywords: expectation gap; auditor and audit processes; responsibility auditor; auditor performance attributes; communication of audit results.Abstrak. Penelitian ini bertujuan untuk mendapatkan bukti empiris mengenai persepsi antara auditor dan mahasiswa akuntansi terhadap Expectation gap dalam isu auditor dan proses audit, tanggung jawab auditor, atribut kinerja auditor dan komunikasi hasil audit. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif komparatif. Adapun responden dalam penelitian ini adalah 30 Auditor yang mewakili Kantor Akuntan Publik di Bandung dan 30 Mahasiswa Akuntansi dari Universitas Sangga Buana YPKP Bandung dan Universitas Maranatha Bandung Untuk mengolah data tersebut digunakan Uji Mann Whitney (U Test). Berdasarkan hasil penelitian menunjukkan bahwa terdapat perbedaan persepsi yang signifikan antara auditor dan mahasiswa akuntansi dalam isu auditor dan proses audit, serta komunikasi hasil audit. Sedangkan untuk isu tanggung jawab auditor dan atribut kinerja auditor tidak terdapat perbedaan yang signifikan antara auditor dan mahasiswa akuntansiKata Kunci: expectation gap; auditor dan proses audit; tanggung jawab auditor; atribut kinerja auditor; komunikasi hasil audit.